PENGARUH RASIO LANCAR DAN RASIO HUTANG TERHADAP PROFITABILITAS PADA INDUSTRI TELEKOMUNIKASI YANG LISTING DI BURSA EFEK INDONESIA - Hamid Halin (Universitas Indo Global Mandiri)
This study aims to determine the effect of the current ratio and debt ratio to profitability in the Telecommunications Industry Listed in Indonesia Stock Exchange. Further research using this term to the current ratio variable current ratio and debt-to-equity ratio / DER for variable rate debt and variable profitability using proxy return on equity / ROE. There were three (3) the company's largest telecom operator in Indonesia in terms of total assets and total revenues and the observation period 2011-2015. The data used is secondary data obtained from the financial statements of each of the companies that were sampled and then the data were analyzed using statistical tools linear regression. The study found that simultaneous current ratio and debt-to-equity ratio / DER significant influence (real) against the return on equity in the Telecommunications Industry Listed in Indonesia Stock Exchange, but partially the current ratio and debt-to-equity ratio / DER no effect significant (real) against the return on equity in the Telecommunications Industry Listed in Indonesia Stock Exchange. Key words: current ratio, DER and ROE